Kolaborasi Model Pentahelix dalam Pengembangan Desa Wisata Pandean Kecamatan Gondang Kabupaten Trenggalek - Yesayabela, Tito Mariano; Satyas, Farhan Ramadany; Musleh, Moh; Rianto, Budi (Kolaborasi : Jurnal Administrasi Publik, 2023)
Pandean Tourism Village is a village which is one of the most popular tourist destinations and is visited by many tourists in Trenggalek Regency. In developing tourist villages, there needs to be collaboration between stakeholders. This article adopts the collaborative perspective of the Penta Helix model to discuss stakeholder interactions, highlight the level of success, and identify several problems in the development of the Pandean Tourism Village. This qualitative research uses a case study approach and visualises collective interactions between stakeholders, including the following: 1) Academic, 2) Business, 3) Community, 4) Government and 5) Media based on the Penta Helix model from Arif Yahya (2016). Data was collected through observation, semi-structured interviews, and document review. The research results show that each of the five stakeholders has played a role according to their field in the development of the Pandean Tourism Village, but cooperation between the stakeholders is still not optimal. The findings of this research recommend that the Village Government's role must be enhanced by developing policies that increase innovation in using local natural resources and institutionalising stakeholder collaboration to ensure sustainable collaboration.